Association between visceral adipose surrogates and infertility among reproductive-aged females: a cross-sectional study - Guo, Dongli; Wang, Ruiya (Frontiers in Endocrinology, 2024)
Background: Visceral adipose tissue (VAT) exerts a substantial influence on female infertility. Nevertheless, the relationship between VAT surrogates and female infertility remains ambiguous.This study employed a cross-sectional design and analyzed data from the National Health and Nutrition Examination Survey (NHANES, 2012(NHANES, -2016)). Weighted logistic regression models were utilized to examine the association between VAT surrogates and infertility. Furthermore, Receiver Operating Characteristic (ROC) curve analysis was conducted to assess the diagnostic efficacy of these surrogates for infertility.: Individuals experiencing infertility exhibited markedly elevated levels of the Chinese Visceral Adiposity Index (CVAI) (108.30 vs. 69.86, P<0.001) and Visceral Adiposity Index (VAI) (1.68 vs. 1.35, P<0.001). When considered as a continuous variable, CVAI (odds ratio [OR]: 1.06, 95% confidence interval [CI]: 1.03-1.09, P<0.001), rather than VAI (OR:1.02, 95%CI: 0.98-1.06, P=0.259), demonstrated a significant association with the risk of female infertility. Consistent findings were also evident after dividing participants into 4 subgroups based on CVAI quartiles. Additionally, ROC curves indicated that CVAI exhibited the most robust diagnostic value for female infertility compared to other indices. Subgroup analyses revealed a robust association between CVAI and infertility across different populations. Conclusion: Females with elevated CVAI levels faced a significantly heightened risk of infertility in the United States. CVAI holds promise as a valuable tool for stratifying the risk of infertility.